Native English: ESL learners’ perceptions of female speakers’ accents - Pilus, Zahariah; Zakaria, Nur Shahida; Zakaria, Muhamad Khairul (2016)
This paper presents some preliminary findings of a study which investigates undergraduate ESL learners’ perceptions of British, American, Australian and New Zealand English accents. The participants were 66 Malaysian undergraduates from a public university in Malaysia. They were presented with speech samples of four female native speakers reading a short passage. The students were asked to rate the speakers for a number of items including the ease of understanding, sounding comfortable to the ears, being an ideal English teacher and being a speaker they would want to sound like. The learners were also asked to state the nationalities of the speakers. In general, the study found that the speakers whose accents were familiar to the learners were rated higher in terms of the items examined. The study also found that the speakers whose accents were familiar to the learners were better identified for their nationalities than those whose accents were less familiar to them. Pedagogical implications of these findings on English language teaching and learning in Malaysia are discussed.